(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2012)
Some important physico-chemical properties of surface water around DEPZ industrial area, Savar were studied to evaluate the water quality. Seven water samples were collected from major waterbodies of DEPZ industrial area. The value of Physico-chemical parameter such as Temperature (57-24°C), pH (12.45-7.58), EC (12400-2060 ?s/cm), BOD5 (895-63.19 mg/L), TSS (2170-435 mg/L), TDS (6840-1036 mg/L), Turbidity (89.55-32.16 mg/L) and Salinity (7.1-1.0 ppt) were highest in the point source (W1) and began to decline as the waste dispersed through the nearby waterbodies (W2-W7). The result revealed that all the chemical constituents, except a few, were beyond the recommended limit for various uses. The lowest content of DO (0.10 mg/L) and highest content of BOD5 (895 mg/L) in point source waterbody indicate that the industries were releasing large amount of oxygen demanding organic wastes which subsequently affected all the studied waterbody. Among metal content of the study area, the value of Fe (1.331-0.443 mg/L), Zn (0.308-0.134 mg/L), Cu (0.244 0.127 mg/L) and Cr (0.615-0.055 mg/L) were gradually decreased from point source to the remote area. Point source (W1) waterbody had the highest concentration of Cr (0.615 mg/L) which exceeded the safe limit for industrial wastewater. This may be due to various chrome agent used in dyeing purposes. Anionic parameters like F- and PO4 3- were at intolerable limit in some waterbody. The coefficient of correlation analysis among physicochemical properties indicated that all the parameters had significant contribution to pollute the water. The correlation between DO and pH was strongly negative (r=-0.995**). Fe showed positive significant correlation with Zn, Cu and Cr. There was a significant positive interaction of PO4 3- with Cl- and NO3- in case of water quality deterioration. The above findings showed that the surface water around DEPZ industrial area was highly polluted by the industrial activities and was harmful for life. DOI: http://dx.doi.org/10.3329/bjsir.v47i3.13061 Bangladesh J. Sci. Ind. Res. 47(3), 279-286, 2012